Evaluasi Website Sekolah Tinggi Ilmu Kesehatan (STIKES) Yayasan Rumah Sakit Dr. Soetomo Menggunakan Metode HOT-Fit - Aprilia Putri Maulidiyah Hasan; Nabila Oktavia Anggraini; Nadzwa Putri Hermawan; Zacky Rensa Putra Listyanto; Dyan Angesti (Jurnal Riset Multidisiplin Edukasi, 2025)
The study was conducted with the aim of evaluating the quality and suitability of website through the applicationof the Human, Organization, and Technology-Fit (HOT-Fit) model. This evaluation is considered crucial in identifying various factors that influence the success of the implementation and utilization of the website in supporting academic activities, administration, and information dissemintaionin the STIKES Yayasan Rumah Sakit Dr.Soetomo environment. In its implementation, the HOT-Fit method is used as an analytical framework to test the aligment between the human (user), organizational (environment and support), and technological (features and functionality) dimensions of the website. The data collection process involed distributing a questionnaire survey to students. The data that was successfully collected was then analyzed quantitatively using descriptive and inferential statistical technique. The analysis aims to identify the level of suitability between the three HOT-Fit dimensions and the influence of each dimension on the level of user satisfaction and the net benefits they feel. Through this study, it is expected to produce comprehensive recommendations for the management. Soetomo to improve the quality, effectiveness, and efficiency of the website.